Impact of evapotranspiration on ecosystem services values in rubber (Hevea brasiliensis L.) plantations: insights into climate change and rubber plantation expansion in Southwestern China - Ling, Zhen; Xia, Tiyuan; Su, Yuan; He, Guangxiong; Gu, Shixiang; Zhao, Zhenyu; Chen, Biao (Frontiers in Agronomy, 2025)
IntroductionThe rapid expansion of rubber (Hevea brasiliensis) plantations in Southwestern China has transformed forest-dominated landscapes. However, the hydrological consequences of this land-use change have not been comprehensively quantified.MethodsThis study reconstructed the long-term actual evapotranspiration (ETa_reconstructed) of rubber plantations using the "Kc-ET0" method, which integrates meteorological data and actual crop coefficients (Kc,actual). The coefficient of variation (CV) and the Random Forest (RF) algorithm were employed to identify the key drivers and analyze the spatiotemporal patterns of the reconstructed ETa_reconstructed. Furthermore, we quantitatively evaluated the influence of ETa_reconstructed on major ecosystem service values (ESVs).ResultsOur results showed that rubber plantations expanded at a rate of 12.49 × 10⁴ ha per decade between 2000 and 2022. The annual average ETa_reconstructed was 952 mm, showing an increasing trend of 12 mm per decade since 1970. The ETa_reconstructed exhibited stable interannual variability (CV range: 0.04–0.11) and was significantly positively correlated with maximum temperature, sunshine duration (SSD), and rubber plantation area, but negatively correlated with relative humidity. SSD (28.5%–38.4%) and rubber plantation area (11.4%–20.3%) were identified as the crucial drivers. The optimal ESVs for rubber plantations were achieved at a multi-year average SSD of 4.17 hours, where the reconstructed ETa ranged between 2.0 and 3.0 mm/day, and carbon sequestration and oxygen release reached their peak values.DiscussionIn conclusion, the ETa_reconstructed of rubber plantations, primarily driven by increased sunshine duration, significantly affects their ecosystem service values in Southwestern China. The identified optimal ETa_reconstructed range provides a scientific basis for precise water management in tropical rubber plantations in the context of climate change.